How can fear impact economic decisions in pandemic contexts at the light of decision-making systems? An approach to the Covid-19 case - Neto, J. C.; Caleiro, A. B.; Filipe, J.; Coelho, M.; Askari, G. (International Journal of Business and Systems Research, 2022)
Fear is an important emotion in contexts of uncertainty. With the spread of Covid-19 disease the process of decision making in the day-to-day economic life is studied considering the way how fear can impact these decisions along the pandemic context. Our study allows to analyze the situation in Brazil, the way fear can emerge through a process of communication, particularly involving the media. It is possible to conclude about the importance of studying the impact of fear in this context of pandemic, by observing that fear is involved when individuals make non-optimal decisions in such a process of decision-making systems.